The Influence of Social Media Marketing, and Electronic Word of Mouth on Brand Trust through Brand Experience: Skincare Study Case in Indonesia - Rugati , Devina Pratya; Santoso, Singgih (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2025)
The skin care business in Indonesia in the past decade has grown rapidly along with the increasing number of consumers who care about their physical health and beauty. This study aims to determine the effect of Social Media Marketing and Electronic Word Of Mouth on Brand Experience, and wants to know the effect of Electronic Word Of Mouth on Brand Experience of ERHA Products in the Special Region of Yogyakarta; This study uses a quantitative approach, specifically a survey method using a questionnaire. The sample in this study were 216 consumers of ERHA Products who used the product for the last three months, which were obtained by using purposive sampling technique. The research method uses Structural Equation Modeling (SEM) analysis with the help of AMOS software.   The results of this study indicate that Social Media Marketing and Electronic Word Of Mouth have a positive and significant effect on Brand Experience, and Brand Experience has a positive and significant effect on brand trust.